SUPERVISI KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU DI SDN RANCAEKEK 03 DAN SDN RANCAEKEK 06 - Jamilah, Evie; Aas Purnamasari; Iman Ramadan; Kokom Komalasari; Ifah Khodijah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to obtain information and an overview regarding the implementation of principal supervision in improving teacher performance at SDN Rancaekek 03 and SDN Rancaekek 06. This research method uses a qualitative approach with descriptive data on the grounds that qualitative methods allow researchers to understand in depth the nuances and context of supervision management principals in a particular school. The research informants consisted of teachers, students and school principals who were selected through purposive sampling techniques. Data collection was carried out through interviews, observation and documentation studies of participants. Data were analyzed using qualitative methods. The results of the research showed that the implementation of supervision was based on the needs and goals of the school and was carried out in three stages, namely planning, implementing supervision and follow-up. This research concludes that the role and influence provided by the principal's supervision is very important on teacher performance. Apart from being the job of the principal, academic supervision also has an influence on the quality of teacher performance, which can be obtained from improving and fostering learning aspects needed by teachers as well as providing encouragement in the form of morals so that teachers always remember their main task, namely improving the quality of teaching. It is hoped that these findings can make a contribution. for development in the field of education, especially those related to the supervision of school principals in an effort to improve teacher performance through supervision.